IFN-γ Attenuates Hypoxia-Inducible Factor (HIF) Activity in Intestinal Epithelial Cells through Transcriptional Repression of HIF-1β - Glover, Louise E. (2011)
Numerous studies have revealed that hypoxia and inflammation occur coincidentally in mucosal disorders, such as inflammatory bowel disease. During inflammation, epithelial-expressed hypoxia-inducible factor (HIF) serves an endogenously protective function. In this study, we sought to explore how mucosal immune responses influence HIF-dependent end points. Guided by a screen of relevant inflammatory mediators, we identified IFN-γ as a potent repressor of HIF-dependent transcription in human intestinal epithelial cells. Analysis of HIF levels revealed that HIF-1β, but not HIF-1α, is selectively repressed by IFN-γ in a JAK-dependent manner. Cloning and functional analysis of the HIF-1β promoter identified a prominent region for IFN-γ–dependent repression. Further studies revealed that colonic IFN-γ and HIF-1β levels were inversely correlated in a murine colitis model. Taken together, these studies demonstrated that intestinal epithelial HIF is attenuated by IFN-γ through transcriptional repression of HIF-1β. These observations are relevant to the pathophysiology of colitis (i.e., that loss of HIF signaling during active inflammation may exacerbate disease pathogenesis).